A silica sol free of secondary small particles and its preparation method and application

By preparing the silicon sol under vacuum and introducing auxiliary precipitant agent, the problem of difficult to remove particles with particle size above 5 nm in the prior art is solved, and the density and particle size distribution of the silicon sol are achieved, which significantly improves the surface quality of semiconductor devices and silicon wafers.

CN119774625APending Publication Date: 2025-04-08WANHUA CHEM GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510002965.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, it is difficult to effectively remove particles with a particle size of more than 5 nm when preparing silicon sols, resulting in uneven particle size distribution of silicon sols, affecting the surface quality of semiconductor devices and silicon wafers, and increasing the defect rate.

Method used

By preparing the silica sol under vacuum and introducing auxiliary precipitants such as quaternary ammonium salts during the reaction, the oligosilicate is easier to grow on the original silica sol particles without forming new nuclei, thereby reducing the production of small particles.

Benefits of technology

The excellent density of silicon sol and the concentration of colloidal particle size distribution are achieved, and there are almost no secondary small particles. The defects on semiconductor devices and silicon wafer surfaces can be significantly reduced in CMP polishing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774625A_ABST
    Figure CN119774625A_ABST
Patent Text Reader

Abstract

The present invention discloses a silica sol which is almost free of secondary small particles, a preparation method and an application thereof. The silica sol has the following characteristics: (1) the primary particle size of the colloidal particles is 15-150 nm, the secondary particle size is 36-300 nm, the PDI is between 0.04-0.1, the Di(90) / Di(10) of the particles is between 1.9-2.1, the Di(90) / Di(50) of the particles is between 1.4-1.5, and the proportion of colloidal particles with a colloidal particle circle equivalent diameter less than 10 nm under the TEM field of view is less than 5%; (2) the ratio of the low-field nuclear magnetic wet method specific surface area of ​​the colloidal particles to the dry method gas adsorption BET specific surface area is S N / S B The Q of 29Si-NMR of the colloid particles is between 1 and 3.5. 4 The proportion is 70-72%, Q 3 The proportion is 21-24%, Q 2 The silica sol of the present invention has excellent compactness and concentrated colloidal particle size distribution, and can be used in CMP polishing to reduce defects on the surface of semiconductor devices and silicon wafers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silica sol preparation, and specifically relates to a silica sol free of secondary small particles and a preparation method and application thereof. Background Art

[0002] Silica sol is a colloidal substance obtained by dispersing silicon dioxide particles in water or other solvents. It is widely used in papermaking, catalysts, casting, coatings and other industries. In recent years, high-purity silica sol has been widely used in the polishing of silicon wafers and chemical mechanical polishing (CMP) of semiconductor devices.

[0003] In the manufacturing process of semiconductor devices, dozens of CMP steps are involved, and different CMP processes have different requirements for abrasives, including hardness, surface silanol groups, purity, particle size, morphology, etc. As for purity, the alkoxide method is a relatively mature process for producing ultra-high purity silica sol. The purity of silica sol prepared by the alkoxide method is directly related to the purity of the raw materials.

[0004] In the CMP process used in semiconductor manufacturing, the uneven distribution of silica sol particle size may cause more serious defects on the surface of semiconductor devices and silicon wafers, ultimately leading to a significant decrease in yield. Therefore, as the core raw material of CMP polishing liquid, silica sol particles are expected to have a nearly uniform particle size, a narrow particle size distribution, and no secondary particles, so as to improve the surface quality of polished silicon wafers and semiconductor devices, thereby improving the yield.

[0005] JP7505130B1 removes some small particles in the silica sol by subjecting the prepared silica sol to an aging treatment for a period of time at a relatively high temperature while maintaining a certain pH and heating power. However, only fine particles with a particle size of less than 5 nm can be removed by simple heat treatment, and particles with a particle size of more than 5 nm are difficult to remove. Moreover, heat treatment of the silica sol by heat treatment is not only time-consuming, but also long-term heat treatment may damage the stability of the silica sol, thereby causing the silica sol to agglomerate into large particles during polishing applications, resulting in more defects on the surface of semiconductor devices and silicon wafers after polishing. Summary of the invention

[0006] In view of the problems existing in the above-mentioned prior art, an object of the present invention is to provide a silica sol that contains almost no secondary small particles. The silica sol has excellent density and concentrated particle size distribution of the colloidal particles. It can be used in CMP polishing to reduce defects on the surface of semiconductor devices and silicon wafers.

[0007] Another object of the present invention is to provide a method for preparing the silica sol which contains almost no secondary small particles.

[0008] Another object of the present invention is to provide an application of the silica sol which contains almost no secondary small particles.

[0009] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0010] A silica sol without secondary small particles, the colloidal particles of which have the following characteristics:

[0011] (1) The primary particle size of the colloid particles is 15-150 nm, the secondary particle size is 36-300 nm, the PDI is between 0.04-0.1, the Di(90) / Di(10) of the particles is between 1.9-2.1, the Di(90) / Di(50) of the particles is between 1.4-1.5, and the proportion of colloid particles with an equivalent circle diameter of less than 10 nm under the TEM field of view is less than 5%;

[0012] (2) Ratio of the low-field NMR wet specific surface area of ​​the colloid to the dry gas adsorption BET specific surface area S N / S B Between 1-3.5, the Q4 ratio of the 29Si-NMR of the colloid particles is 70-72%, Q3 is 21-24%, and Q2 is 5%-7%.

[0013] On the other hand, the method for preparing the silica sol without secondary small particles comprises the following steps:

[0014] (1) preparing liquid A: uniformly mixing an organic solvent, water, and an alkali catalyst to prepare liquid A;

[0015] (2) preparing liquid B: uniformly mixing an organic solvent and alkoxysilane to form liquid B;

[0016] (3) Under vacuum conditions, the temperature of liquid A is heated to its boiling point. During the reaction, the steam is recondensed to allow the liquid to flow back into the reactor. Liquid B is added dropwise to liquid A. After the addition is completed, the reaction is allowed to proceed for a period of time to obtain an initial silica sol C1.

[0017] (4) mixing alkoxysilane and water, and fully hydrolyzing them to obtain C2, which is used as a silicon source for regrowth;

[0018] (5) Using C1 as the base liquid, adding an auxiliary precipitant to the C1 liquid, adding C2 to C1 for reaction growth, and obtaining the finished silica sol C3;

[0019] (6) The organic solvent in C3 is replaced with ultrapure water, concentrated to more than 20%, and filtered to remove large particles to obtain the silica sol.

[0020] In some specific embodiments, the organic solvent in step 1) and step 2) is one or more of methanol, ethanol, propanol, isopropanol, acetonitrile, acetone, methyl ethyl ketone, diethyl ether, and ethyl propyl ether;

[0021] Preferably, the organic solvent is the same as the alcohol produced by the hydrolysis of alkoxysilane.

[0022] In some specific embodiments, the water in step 1) is ultrapure water; preferably, the resistivity of the ultrapure water is ≥10 MΩ·cm, preferably the resistivity is ≥18.2 MΩ·cm;

[0023] In some specific embodiments, the base catalyst in step 1) is selected from at least one of alkali metal hydroxides, ammonia, organic amines or guanidine compounds;

[0024] Preferably, the alkali metal hydroxide is selected from at least one of potassium hydroxide, sodium hydroxide and lithium hydroxide;

[0025] The organic amine is selected from one or more of primary amine, secondary amine, tertiary amine and quaternary amine; and / or

[0026] The guanidine compound is selected from at least one of tetramethylguanidine, trimethylguanidine and guanidine carbonate;

[0027] More preferably, in the liquid A of step 1), the mass fraction of the organic solvent is 0%-90%, the mass fraction of the water is 10%-99.5%, and the mass fraction of the base catalyst is 0.5%-5%.

[0028] In some specific embodiments, the alkoxysilane in step 2) is at least one of tetramethoxysilane, tetraethoxysilane, and tetrapropoxysilane, preferably tetramethoxysilane;

[0029] Preferably, the volume ratio of the organic solvent to the alkoxysilane is 1:10-10:1, and the molar ratio of the alkoxysilane to the water in step (1) is less than 1;

[0030] More preferably, the volume ratio of the organic solvent to the alkoxysilane is 1:5-1:1, and the molar ratio of the alkoxysilane to the water in step (1) is less than 1:4.

[0031] In some specific embodiments, the dropwise addition time of the solution B to the solution A in step 3) is 0.1 min to 40 min, preferably 0.1 min to 20 min;

[0032] Preferably, the reaction temperature after the dropwise addition is between 5-90°C, preferably 20-70°C.

[0033] In some specific embodiments, after the alkoxysilane is fully hydrolyzed in step 4), the mass fraction of silicon dioxide is between 3% and 12%, preferably 3% to 9%;

[0034] Preferably, the alkoxysilane is the same as the alkoxysilane described in step 2).

[0035] In some specific embodiments, the auxiliary precipitant in step 5) is one or more of a soluble metal salt or a quaternary ammonium salt;

[0036] Preferably, the soluble metal salt is selected from at least one of sodium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate, magnesium nitrate and calcium nitrate; the general formula of the quaternary ammonium salt is R1R2R3R4NX, wherein R1, R2, R3 and R4 are alkyl groups, R1, R2, R3 and R4 are the same or different, X is a halogen anion or an acid radical, and the auxiliary precipitant is preferably one or more quaternary ammonium salts;

[0037] More preferably, the amount of the auxiliary precipitant added is 500ppm-3000ppm, relative to the total amount of the added alkoxysilane converted into the total mass of silicon dioxide;

[0038] Further preferably, in step 5), the reaction temperature is 5-90°C, preferably 20-70°C, and the dropwise addition time of C2 to C1 is 1-30h, preferably 2-15h.

[0039] In some specific embodiments, the solvent replacement in step 6) is performed by adding ultrapure water while heating to evaporate and remove the solvent in the water, or

[0040] Using ultrafiltration, while replenishing ultrapure water, concentrating until the solvent content in the silica sol is removed to below 200 ppm, preferably below 100 ppm;

[0041] Preferably, the concentration in step 4) is performed by vacuum heating concentration or ultrafiltration membrane concentration to concentrate the mass fraction of the silica sol to more than 20%;

[0042] More preferably, in step 6), the filtering accuracy is 0.1 μm-5 μm.

[0043] On the other hand, the aforementioned silica sol free of secondary small particles or the silica sol free of secondary small particles prepared by the aforementioned preparation method is used in chemical mechanical polishing.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1) The method of the present invention avoids uneven particle distribution caused by reaction exotherm by preparing silica sol under vacuum, and introduces an auxiliary precipitant during the preparation of silica sol, so that silicate is more likely to grow by adhering to the original silica sol particles without forming new nuclei, thereby reducing the number of small particles and promoting condensation between silicate, increasing the density of particles, thereby promoting the polishing rate.

[0046] 2) The method of the present invention avoids the subsequent long-term aging process, and can avoid the formation of small particles in the synthesis stage of silica sol, thereby simplifying the process flow, shortening the post-treatment process, and greatly improving the efficiency.

[0047] 3) The silica sol of the present invention contains almost no secondary small particles, has excellent compactness, and has a concentrated distribution of colloidal particle sizes. It can be used in CMP polishing to reduce defects on the surface of semiconductor devices and silicon wafers. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a TEM image of the silica sol of Example 1 of the present invention.

[0049] Figure 2 This is a TEM image of the silica sol of Comparative Example 1 of the present invention.

[0050] Figure 3 This is a TEM image of the silica sol of Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0051] In order to understand the technical features and content of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. For those who do not specify specific conditions in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer.

[0052] A method for preparing a silica sol free of secondary small particles comprises the following steps:

[0053] 1) Prepare Liquid A: Evenly mix a certain amount of organic solvent, water and alkaline catalyst to form Liquid A;

[0054] 2) Prepare liquid B: uniformly mix a certain amount of organic solvent and alkoxysilane to form liquid B;

[0055] 3) Under a certain vacuum degree, the temperature of liquid A is heated to its boiling point. During the reaction, the steam is recondensed to allow the liquid to flow back into the reactor. Liquid B is added dropwise to liquid A at a certain speed. After the addition is completed, the reaction is carried out for a period of time to obtain the initial silica sol C1;

[0056] 4) Mix a certain amount of alkoxysilane and water, and after sufficient hydrolysis, obtain C2, which is used as a silicon source for regrowth;

[0057] 5) Using C1 as the base liquid, adding a certain amount of auxiliary precipitant to the C1 liquid, adding C2 to C1 at a certain temperature and at a certain speed to obtain the finished silica sol C3;

[0058] 6) The organic solvent in C3 is replaced with ultrapure water, and concentrated to 20% or more, and large particles are removed by filtration to obtain the above-mentioned silica sol.

[0059] In the present invention, the organic solvent described in step 1) and step 2) is one or more of methanol, ethanol, propanol, isopropanol, acetonitrile, acetone, methyl ethyl ketone, diethyl ether, ethyl propyl ether, etc.; preferably, the solvent is the same as the alcohol produced by the hydrolysis of alkoxysilane, preferably a small molecule alcohol, such as methanol, ethanol, propanol, isopropanol, etc.

[0060] In step 1), the water is ultrapure water, and the resistivity of the ultrapure water is ≥15 MΩ·cm, such as 15 MΩ·cm, 16 MΩ·cm, 17 MΩ·cm, 18 MΩ·cm, preferably ≥18.0 MΩ·cm.

[0061] In step 1), the base catalyst is selected from at least one of alkali metal hydroxides, ammonia water, organic amines or guanidine compounds; preferably, the alkali metal hydroxide is selected from at least one of potassium hydroxide, sodium hydroxide and lithium hydroxide; the organic amine is selected from one or more of primary amines, secondary amines, tertiary amines and quaternary amines; the guanidine compound is selected from at least one of tetramethylguanidine, trimethylguanidine and guanidine carbonate. Ammonia water and organic amines are preferred.

[0062] In the liquid A of step 1), the mass fraction of the organic solvent is 0%-90%, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, etc., the mass fraction of the ultrapure water is 10%-99.5%, for example, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, etc., and the mass fraction of the base catalyst is 0.5%-5%, for example, 1%, 2%, 3%, 4%, 5%, etc., based on the total mass of liquid A.

[0063] In step 2), the alkoxysilane is one or more of tetramethoxysilane, tetraethoxysilane, and tetrapropoxysilane, preferably tetramethoxysilane.

[0064] In step 2), the volume ratio of the organic solvent to the alkoxysilane is 1:10-10:1, such as 1:5, 1:4, 1:3, 1:2, 1:1, preferably 1:5-1:1. The molar ratio of the alkoxysilane to water is less than 1:1, such as 1:2, 1:3, 1:4, 1:5, etc.

[0065] In step 3), in the preparation of the initial silica sol, under vacuum conditions, the temperature of liquid A is heated to its boiling point, that is, heated to boiling, and the steam is kept to be recondensed during the reaction process, so that the liquid is refluxed into the reactor, and liquid B is added dropwise to liquid A, and the dropwise addition time of liquid B to liquid A is 0.1min-40min, preferably 0.1min-20min, such as 1min, 2min, 3min, 5min, 10min, 15min, 20min. After the dropwise addition is completed, the reaction is carried out for a period of time, and the reaction temperature is between 5-90°C, such as 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, etc., preferably 20-70°C, and the initial silica sol C1 is obtained by reaction.

[0066] In step 4), after the alkoxysilane is fully hydrolyzed, the mass fraction of silicon dioxide is between 3% and 12%, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%, preferably 3% to 9%. Wherein, the alkoxysilane is one or more of tetramethoxysilane, tetraethoxysilane, and tetrapropoxysilane, preferably tetramethoxysilane, and more preferably the same as in step 2).

[0067] In step 5), the auxiliary precipitant is one or more soluble metal salts or quaternary ammonium salts, wherein the soluble metal salts are such as sodium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate, magnesium nitrate, calcium nitrate, etc.; the general formula of the quaternary ammonium salt is R1R2R3R4NX, wherein R1, R2, R3, R4 are organic groups, R1, R2, R3, R4 may be the same or different, the number of carbon atoms of the organic group R is ≤18, and X is a halogen anion (F-, Cl-, Br-, I-), or an acid radical (RCOO - 、HSO4 - Preferably, the auxiliary precipitant is one or more quaternary ammonium salts; preferably, a short-chain quaternary ammonium salt or an aromatic quaternary ammonium salt in which the carbon number of the organic group R is ≤10.

[0068] The amount of the auxiliary precipitant added is between 500ppm and 3000ppm relative to the amount of silicon dioxide converted to the total alkoxysilane added, for example, 500ppm, 600ppm, 700ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm.

[0069] In step 5), the auxiliary precipitant is added to the C1 primer, and then C2 is added to C1 for reaction growth. The reaction temperature is between 5-90°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, preferably 20-70°C; the dropwise addition time of C2 to C1 is 1-30h, for example, 1h, 2h, 3h, 4h, 5h, 10h, 15h, 20h, 25h, 30h, etc.

[0070] In step 6), the organic solvent is replaced by adding ultrapure water while heating to evaporate the solvent in the water, or by ultrafiltration to add ultrapure water while concentrating until the solvent content in the silica sol is removed to less than 200 ppm, preferably less than 100 ppm; more preferably, the concentration in step 6) is concentrated by vacuum heating concentration or ultrafiltration membrane concentration to concentrate the mass fraction of the silica sol to more than 20%.

[0071] In step 6), the filtration accuracy of filtering out large particles is 0.1 μm-5 μm.

[0072] In the present invention, unless otherwise specified, reference may be made to the prior art, for example, replacing the organic solvent with ultrapure water, concentrating it to more than 20%, and filtering out large particles, which are conventional technical means in the art. The present invention has no particular limitation and reference may be made to the prior art.

[0073] The preparation method of the present invention is further explained below by more specific examples, but does not constitute any limitation.

[0074] The main detection methods involved in the following embodiments are as follows:

[0075] The secondary particle size, PDI and particle size distribution of silica sol particles were measured by Malvern Zetasizer Nano ZS90, and the primary particle size was measured by BET specific surface area method to obtain the specific surface area S B , primary particle size is 2727 / S bet The degree of association is the ratio of the secondary particle size to the primary particle size.

[0076] The apparent morphology of the silica sol and the number of particles with a circular equivalent diameter were characterized by TEM. The TEM field of view was randomly selected, and the proportion of particles with a diameter less than 10 nm in the total number of particles was counted.

[0077] The true density is tested by a true density meter.

[0078] The Q silicon content of the particles was tested using a Bruker AVANCE NEO 600M spectroscopy instrument, and the test conditions were as follows: test probe 4 mm MAS probe, test core 29Si; test sequence: HPDEC; D1 = 30 seconds, NS = 1024, SW = 400 ppm, O1 = -105 ppm, pulse frequency = 60 KHz, rotation speed 10 KHz.

[0079] The low-field nuclear magnetic resonance wet specific surface area of ​​the particles was tested by a low-field nuclear magnetic resonance particle surface characteristics analyzer, and the test conditions were as follows: the test sequence was CPMG, TW=18000ms, TE=1.5ms, NECH=18000, PRG=2.

[0080] The polishing test of silica sol particles was conducted by using the polishing liquid formula and polishing test conditions of Example 6 in patent CN 118496768B. LPC is the number of defects on the wafer surface after polishing.

[0081] The main sources of raw materials involved in the embodiments of the present invention are as follows:

[0082]

[0083]

[0084] Example 1

[0085] 117.75g methanol, 70.55g water and 3.8g ammonia water were mixed and stirred evenly as liquid A. Under vacuum, the reaction liquid was kept in a boiling state and the reaction temperature was controlled at 25°C. 15ml methanol and 5ml tetramethoxysilane (TMOS) were mixed evenly as liquid B. Liquid B was added to liquid A using a peristaltic pump. The addition was completed in 20 minutes. After the addition was completed, the reaction was continued for 30 minutes to obtain the initial silica sol. The above initial silica sol was taken, and hexadecyltrimethylammonium bromide (CTAB) with a concentration of 500ppm relative to silica was added thereto. After mixing evenly, it was used as a primer. 25ml TMOS and 308ml water were taken and stirred and mixed evenly until they were completely clear and transparent to prepare a 3% silicic acid aqueous solution. At 40°C, the above silicic acid aqueous solution was added dropwise to the primer at a speed of 3ml / min. After the addition was completed, the aging reaction was continued for 2h, and then ultrapure water was added while evaporating until the content of organic matter in the silica sol dropped to below 100ppm and concentrated to more than 20%. The primary particle size of the obtained silica sol is 40nm, the secondary particle size is 75nm, the PDI is 0.06, the Di(90) / Di(10) of the particles is 1.91, and the Di(90) / Di(50) of the particles is 1.42; the proportion of particles with a circle equivalent diameter of less than 10nm under the TEM field of view is 0, and the low-field nuclear magnetic wet method specific surface area S N 180m 2 / g, dry gas adsorption BET specific surface area S B 68m 2 / g,S N / S B The 29Si-NMR of the colloidal particles is 2.65, Q4 accounts for 70%, Q3 accounts for 23%, and Q2 accounts for 7%. After polishing with this silica sol as an abrasive, the LPC of the wafer surface is 10.

[0086] Example 2

[0087] 117.75g of ethanol, 70.55g of water and 7.61g of tetramethylammonium hydroxide were mixed and stirred uniformly as liquid A. Under vacuum, the reaction liquid was boiled and the reaction temperature was controlled at 40°C. 10ml of ethanol and 5ml of tetraethoxysilane (TEOS) were mixed uniformly as liquid B. Liquid B was added to liquid A using a peristaltic pump. The addition was completed in 30 minutes. After the addition was completed, the reaction was continued for 30 minutes to obtain an initial silica sol. The above initial silica sol was taken, and tetramethylammonium hydrochloride of 1000ppm relative to silicon dioxide was added thereto. After mixing uniformly, it was used as a primer. 25ml of TMOS and 308ml of water were taken and stirred and mixed uniformly until it was completely clear and transparent to prepare a 3% silicic acid aqueous solution. At 60°C, the above silicic acid aqueous solution was dripped into the primer at a speed of 3ml / min. After the dripping was completed, the aging reaction was continued for 2h, and then ultrapure water was added while evaporating until the content of organic matter in the silica sol dropped to below 100ppm and concentrated to more than 20%. The primary particle size of the obtained silica sol is 30nm, the secondary particle size is 60nm, the PDI is 0.05, the Di(90) / Di(10) of the particles is 1.9, and the Di(90) / Di(50) of the particles is 1.4; the proportion of particles with a colloidal particle circle equivalent diameter less than 10nm under the TEM field of view is 0, and the low-field nuclear magnetic wet method specific surface area S N 100m 2 / g, dry gas adsorption BET specific surface area S B 91m 2 / g,S N / S B The 29Si-NMR of the colloidal particles is 71% for Q4, 24% for Q3, and 5% for Q2. After polishing with this silica sol as an abrasive, the LPC of the wafer surface is 12.

[0088] Example 3

[0089] 117.75g of water, 70.55g of methanol and 7g of ammonia water were mixed and stirred evenly as liquid A. Under vacuum, the reaction liquid was boiled and the reaction temperature was controlled at 60°C. 5ml of methanol and 5ml of tetramethoxysilane (TMOS) were mixed evenly as liquid B. Liquid B was added to liquid A using a peristaltic pump. The addition was completed in 20 minutes. After the addition was completed, the reaction was continued for 30 minutes to obtain an initial silica sol. The above initial silica sol was taken, and tetraethylammonium hydrochloride of 1500ppm relative to silicon dioxide was added thereto. After mixing evenly, it was used as a primer. 50ml of TMOS and 308ml of water were taken and stirred and mixed evenly until it was completely clear and transparent to prepare a 6% silicic acid aqueous solution. At 40°C, the above silicic acid aqueous solution was added dropwise to the primer at a speed of 0.5ml / min. After the addition was completed, the aging reaction was continued for 2h, and then ultrapure water was added while evaporating until the content of organic matter in the silica sol dropped to less than 100ppm and concentrated to more than 20%. The primary particle size of the obtained silica sol is 35nm, the secondary particle size is 70nm, the PDI is 0.06, the Di(90) / Di(10) of the particles is 2.0, and the Di(90) / Di(50) of the particles is 1.45; the proportion of particles with a colloidal particle circle equivalent diameter less than 10nm under the TEM field of view is 0, and the low-field nuclear magnetic wet method specific surface area SN of the colloidal particles is 80m 2 / g, dry gas adsorption BET specific surface area S B 78m 2 / g,S N / S B The 29Si-NMR of the colloidal particles is 1.03, Q4 accounts for 72%, Q3 accounts for 23%, and Q2 accounts for 5%. After polishing with this silica sol as an abrasive, the LPC of the wafer surface is 13.

[0090] Example 4

[0091] 117.75g methanol, 70.55g water and 7.61g ammonia water were mixed and stirred evenly as liquid A. Under vacuum, the reaction liquid was kept in a boiling state and the reaction temperature was controlled at 25°C. 15ml methanol and 5ml tetramethoxysilane (TMOS) were mixed evenly as liquid B. Liquid B was added to liquid A using a peristaltic pump. The addition was completed in 20 minutes. After the addition was completed, the reaction was continued for 30 minutes to obtain the initial silica sol. The above initial silica sol was taken, and 500ppm of tetramethylammonium oxalate relative to silicon dioxide was added thereto. After mixing evenly, it was used as a primer. 25ml TMOS and 308ml water were taken and stirred and mixed evenly until they were completely clear and transparent to prepare a 3% silicic acid aqueous solution. At 40°C, the above silicic acid aqueous solution was added dropwise to the primer at a speed of 3ml / min. After the addition was completed, the aging reaction was continued for 2h, and then ultrapure water was added while evaporating until the content of organic matter in the silica sol dropped to below 100ppm and concentrated to more than 20%. The primary particle size of the obtained silica sol is 41nm, the secondary particle size is 79nm, the PDI is 0.06, the Di(90) / Di(10) of the particles is 2, and the Di(90) / Di(50) of the particles is 1.5; the proportion of particles with a circle equivalent diameter of less than 10nm under the TEM field of view is 0, and the low-field nuclear magnetic wet method specific surface area SN of the particles is 180m 2 / g, dry gas adsorption BET specific surface area S B 66.5m 2 / g,S N / S B The LPC of the wafer surface is 11 after polishing with this silica sol as abrasive.

[0092] Example 5

[0093] 178.3g water, 10g methanol and 7.61g ethanolamine were mixed and stirred evenly as liquid A. Under vacuum, the reaction liquid was boiled and the reaction temperature was controlled at 50°C. 5ml methanol and 15ml tetramethoxysilane (TMOS) were mixed evenly as liquid B. Liquid B was added to liquid A using a peristaltic pump. The addition was completed in 40 minutes. After the addition was completed, the reaction was continued for 30 minutes to obtain the initial silica sol. The above initial silica sol was taken, and 2500ppm of tetramethylammonium bromide relative to silicon dioxide was added thereto. After mixing evenly, it was used as a primer. 25ml TMOS and 308ml water were taken and stirred and mixed evenly until it was completely clear and transparent to prepare a 3% silicic acid aqueous solution. At 40°C, the above silicic acid aqueous solution was added dropwise to the primer at a speed of 3ml / min. After the addition was completed, the aging reaction was continued for 2h, and then ultrapure water was added while evaporating until the content of organic matter in the silica sol dropped to below 100ppm and concentrated to more than 20%. The primary particle size of the obtained silica sol is 30nm, the secondary particle size is 75nm, the PDI is 0.08, the Di(90) / Di(10) of the particles is 2.1, and the Di(90) / Di(50) of the particles is 1.5; the proportion of particles with a circle equivalent diameter of less than 10nm under the TEM field of view is 0, and the low-field nuclear magnetic wet method specific surface area S N 140m 2 / g, dry gas adsorption BET specific surface area S B 91m 2 / g, SN / SB is 1.54, Q4 accounts for 70.5% of the 29Si-NMR of the colloidal particles, Q3 accounts for 24%, and Q2 accounts for 5.5%. After polishing with this silica sol as an abrasive, the LPC of the wafer surface is 10.

[0094] Comparative Example 1

[0095] 117.75g methanol, 70.55g water and 3.8g ammonia water were mixed and stirred evenly as liquid A. The initial reaction temperature was controlled at 25°C using an oil bath. 15ml methanol and 5ml tetramethoxysilane (TMOS) were mixed evenly as liquid B. Liquid B was added to liquid A using a peristaltic pump. During the addition, the reaction temperature would rise to 28°C under non-vacuum conditions. The addition was completed in 20 minutes. After the addition was completed, the reaction was continued for 30 minutes to obtain an initial silica sol. Take the above initial silica sol, add hexadecyltrimethylammonium bromide (CTAB) with respect to silica 500ppm, mix well and use as primer, take 25ml TMOS and 308ml water and stir and mix well until completely clear and transparent to make 3% silicic acid aqueous solution, add the above silicic acid aqueous solution to the primer at a rate of 3ml / min at 40°C, continue aging reaction for 2h after the addition is complete, then add ultrapure water while evaporating until the content of organic matter in the silica sol drops below 100ppm and is concentrated to more than 20%. The primary particle size of the silica sol obtained is 35nm, the secondary particle size is 50nm, the PDI is 0.15, the Di(90) / Di(10) of the particles is between 2.4, the Di(90) / Di(50) of the particles is 1.6, and the proportion of particles with a colloidal particle circle equivalent diameter less than 10nm under the TEM field of view is 5%. The low-field nuclear magnetic wet method specific surface area S of the colloidal particles N 260m 2 / g, dry gas adsorption BET specific surface area S B 78m 2 / g,S N / S B The 29Si-NMR of the colloidal particles is 3.33, Q4 accounts for 69%, Q3 accounts for 24%, and Q2 accounts for 7%. After polishing with this silica sol as an abrasive, the LPC of the wafer surface is 30.

[0096] Comparative Example 2

[0097] 117.75g methanol, 70.55g water and 3.8g ammonia water were mixed and stirred evenly as liquid A. Under vacuum, the reaction liquid was boiled and the reaction temperature was controlled at 25°C. 15ml methanol and 5ml tetramethoxysilane (TMOS) were mixed evenly as liquid B. Liquid B was added to liquid A using a peristaltic pump. The addition was completed in 20 minutes. After the addition was completed, the reaction was continued for 30 minutes to obtain the initial silica sol. The above initial silica sol was taken as the primer, 25ml TMOS and 308ml water were stirred and mixed evenly until they were completely clear and transparent to prepare a 3% silicic acid aqueous solution. At 40°C, the above silicic acid aqueous solution was added dropwise to the primer at a rate of 3ml / min. After the addition was completed, the aging reaction was continued for 2h, and then ultrapure water was added while evaporating until the content of organic matter in the silica sol dropped to below 100ppm and concentrated to more than 20%. The proportion of colloid particles with a colloidal particle circle equivalent diameter less than 10nm in the TEM field of view of the obtained silica sol was 10%. The primary particle size is 38nm, the secondary particle size is 75nm, the PDI is 0.06, the Di(90) / Di(10) of the particles is 2.05, and the Di(90) / Di(50) of the particles is 1.49; the low-field nuclear magnetic wet method specific surface area S N 200m 2 / g, dry gas adsorption BET specific surface area S B 72m 2 / g,S N / S B The 29Si-NMR of the colloidal particles is 2.78, Q4 accounts for 69.5%, Q3 accounts for 23.5%, and Q2 accounts for 7%. After polishing with this silica sol as an abrasive, the LPC of the wafer surface is 50.

[0098] Comparative Example 3

[0099] The pH of the silica sol prepared in Comparative Example 2 was adjusted to about 10, and heated and aged at 95°C for 30 hours. Under the TEM field of view, the proportion of particles with a circle equivalent diameter of less than 10 nm was reduced to 5%, but some particles still could not be completely removed. After heating, the primary particle size was 38.5 nm, the secondary particle size was 75 nm, the PDI was 0.06, the Di(90) / Di(10) of the particles was 2.05, and the Di(90) / Di(50) of the particles was 1.49; the low-field nuclear magnetic wet method specific surface area S of the particles was 2.5477 nm. N 150m 2 / g, dry gas adsorption BET specific surface area S B 71m 2 / g,S N / S BThe 29Si-NMR of the colloidal particles is 2.11, Q4 accounts for 69.5%, Q3 accounts for 24%, and Q2 accounts for 6.5%. After the silica sol is heated and used as an abrasive, the LPC of the wafer surface after polishing is 42.

[0100] Comparative Example 4

[0101] Silica sol was prepared according to the method of patent JP7505130B1: solution A was a mixture of 976 g methanol, 97 g water and 58 g 29% ammonia water, solution B was a mixture of 190 g methanol and 506 g tetramethoxysilane (TMOS), and solution C was a mixture of 119 g pure methanol. Water (pH = 7.85) was added at a constant rate over 75 minutes. When preparing the reaction solution, the temperature of each solution was maintained at 35°C before mixing, and the temperature of the reaction solution was adjusted from the initial reaction temperature of 35°C (at the beginning of addition) when solution B was added to solution A. The total amount of solution B and solution C was added to solution A at a constant rate, while controlling the temperature so that the final reaction temperature was reduced to 24.5°C at the end (at the end of synthesis). Synthesis). The reaction solution was heated and concentrated under stirring conditions, and heated and replaced with water. The methanol concentration after heating and replacing water was 301 ppm. 0.65 parts by mass of 3-ethoxypropylamine (3-EOPA) was added to 100 parts by mass of the heated water-substituted silica sol obtained above, the pH was adjusted to 9.9, and the silica sol was heated at 50°C. 100°C under normal pressure. When the silica sol reached 100°C, the heat treatment was started, and samples were taken every 0.5 hours from the start of the heat treatment to measure the pH. 0.5 hours after the start of the heat treatment, the pH was 9.6, so 0.2 parts by mass of 3-EOPA was added again to adjust the pH to 9.9. The above operation was performed every 1.5 hours from the start of the heat treatment to the end of the heat treatment. 2.2 parts by mass of 3-EOPA were added from the start of the heat treatment to the end of the heat treatment. The above heat treatment was performed for 16 hours to obtain colloidal silica. The primary particle size of the obtained silica sol is 58.8nm, the secondary particle size is 90.8nm, the PDI is 0.12, the Di(90) / Di(10) of the particles is 2.03, and the Di(90) / Di(50) of the particles is 1.59; the proportion of particles with a colloidal particle circle equivalent diameter less than 10nm under the TEM field of view is 3%, and the low-field nuclear magnetic wet method specific surface area S N 72m 2 / g, dry gas adsorption BET specific surface area S B 46.37m 2 / g,S N / S B The 29Si-NMR of the colloidal particles is 1.55, Q4 accounts for 69%, Q3 accounts for 24%, and Q2 accounts for 7%. After polishing with this silica sol as an abrasive, the LPC of the wafer surface is 45.

[0102] Table 1 Example and comparative example data table

[0103]

[0104] In Examples 1-5, during the preparation of the initial silica sol, the temperature of the reaction system was controlled by vacuuming, thereby avoiding the temperature rise caused by the exothermic reaction and making the prepared silica sol particles evenly distributed. During the particle regrowth process, the oligosilicic acid was more easily deposited on the original silica sol particles by introducing quaternary ammonium salt into the reaction system, without forming new nuclei, thereby avoiding the generation of secondary particles. Figure 1 It can be seen that the equivalent circular diameters of the silica sols prepared under vacuum conditions are nearly the same, while in Comparative Example 1, during the preparation of the initial silica sol, the reaction temperature was controlled by an oil bath hot and cold cycle integrated machine. During the reaction, the temperature of the entire system rose due to heat release, resulting in a smaller particle size of the prepared silica sol and a wider particle size distribution. Figure 2 It can be seen that the equivalent diameters of the silica sols prepared under non-vacuum conditions vary, and the silica sol particles obtained are distributed widely. From the CMP application evaluation, the silica sol with a wide particle size distribution in Comparative Example 1 is used as an abrasive, and the number of defects on the wafer surface after polishing is three times that in Example 1. In Comparative Example 2, during the regrowth of the silica sol, no auxiliary precipitant quaternary ammonium salt is added, and the silica sol finally obtained contains secondary particles, such as Figure 3 As shown in the CMP application evaluation, the small particles in Comparative Example 2 lead to more defects after polishing than in Example 1. Compared with Example 1, the S N / S B The value increases, and the proportion of Q4 decreases significantly, indicating that the density of the particles decreases. Although Comparative Example 3 reduces secondary particles through the post-treatment process of heat aging, this method cannot completely remove small particles, and the post-treatment process is time-consuming and inefficient. In addition, the number of defects on the wafer after polishing in Comparative Example 3 is greater than that in Comparative Example 2. This may be because the stability of the silica sol decreases during the heating process, and flocculation occurs during the preparation of the slurry, resulting in an increase in the number of defects after polishing. Comparative Example 4 prepares silica sol according to the method of the prior art. Under the TEM field of view, the proportion of colloid particles with a circular equivalent diameter of less than 10 nm is 3%, and the particle size distribution is wide. The defects on the wafer surface after polishing are more than those of the silica sol prepared by the method of the present invention.

[0105] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A silica sol free of secondary small particles, characterized in that: Meet the following characteristics: (1) The primary particle size of the colloid particles is 15-150 nm, the secondary particle size is 36-300 nm, the PDI is between 0.04-0.1, the Di(90) / Di(10) of the particles is between 1.9-2.1, the Di(90) / Di(50) of the particles is between 1.4-1.5, and the proportion of colloid particles with an equivalent circle diameter of less than 10 nm under the TEM field of view is less than 5%; (2) Ratio of the low-field NMR wet specific surface area of ​​the colloid to the dry gas adsorption BET specific surface area S N / S B Between 1-3.5, the Q4 ratio of the 29Si-NMR of the colloid particles is 70-72%, Q3 is 21-24%, and Q2 is 5%-7%.

2. The method for preparing the silica sol free of secondary small particles according to claim 1, characterized in that: The following steps are involved: (1) preparing liquid A: uniformly mixing an organic solvent, water, and an alkali catalyst to prepare liquid A; (2) preparing liquid B: uniformly mixing an organic solvent and alkoxysilane to form liquid B; (3) Under vacuum conditions, the temperature of liquid A is heated to its boiling point. During the reaction, the steam is recondensed to allow the liquid to flow back into the reactor. Liquid B is added dropwise to liquid A. After the addition is completed, the reaction is allowed to proceed for a period of time to obtain an initial silica sol C1. (4) mixing alkoxysilane and water, and fully hydrolyzing them to obtain C2, which is used as a silicon source for regrowth; (5) Using C1 as the base liquid, adding an auxiliary precipitant to the C1 liquid, adding C2 to C1 for reaction growth, and obtaining the finished silica sol C3; (6) The organic solvent in C3 is replaced with ultrapure water, concentrated to more than 20%, and filtered to remove large particles to obtain the silica sol.

3. The preparation method according to claim 2, characterized in that: The organic solvent in step 1) and step 2) is one or more of methanol, ethanol, propanol, isopropanol, acetonitrile, acetone, methyl ethyl ketone, diethyl ether, and ethyl propyl ether; Preferably, the organic solvent is the same as the alcohol produced by the hydrolysis of alkoxysilane.

4. The preparation method according to claim 2 or 3, characterized in that: The water in step 1) is ultrapure water; preferably, the resistivity of the ultrapure water is ≥10MΩ·cm, preferably the resistivity is ≥18.2MΩ·cm; and / or The base catalyst in step 1) is selected from at least one of alkali metal hydroxides, ammonia, organic amines or guanidine compounds; Preferably, the alkali metal hydroxide is selected from at least any one of potassium hydroxide, sodium hydroxide and lithium hydroxide; and / or The organic amine is selected from one or more of primary amine, secondary amine, tertiary amine and quaternary amine; and / or The guanidine compound is selected from at least one of tetramethylguanidine, trimethylguanidine and guanidine carbonate; More preferably, in the liquid A of step 1), the mass fraction of the organic solvent is 0%-90%, the mass fraction of the water is 10%-99.5%, and the mass fraction of the base catalyst is 0.5%-5%.

5. The preparation method according to claim 2, characterized in that: The alkoxysilane in step 2) is at least one of tetramethoxysilane, tetraethoxysilane and tetrapropoxysilane, preferably tetramethoxysilane; Preferably, the volume ratio of the organic solvent to the alkoxysilane is 1:10-10:1, and the molar ratio of the alkoxysilane to the water in step (1) is less than 1; More preferably, the volume ratio of the organic solvent to the alkoxysilane is 1:5-1:1, and the molar ratio of the alkoxysilane to the water in step (1) is less than 1:

4.

6. The preparation method according to claim 2, characterized in that: In step 3), the dropwise addition time of liquid B to liquid A is 0.1 min to 40 min, preferably 0.1 min to 20 min; Preferably, the reaction temperature after the dropwise addition is between 5-90°C, preferably 20-70°C.

7. The preparation method according to claim 2, characterized in that: After the alkoxysilane is fully hydrolyzed in step 4), the mass fraction of silicon dioxide is between 3% and 12%, preferably between 3% and 9%; Preferably, the alkoxysilane is the same as the alkoxysilane described in step 2).

8. The preparation method according to claim 2, characterized in that: The auxiliary precipitant in step 5) is one or more of a soluble metal salt or a quaternary ammonium salt; Preferably, the soluble metal salt is selected from at least one of sodium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium nitrate, potassium nitrate, magnesium nitrate and calcium nitrate; the general formula of the quaternary ammonium salt is R1R2R3R4NX, wherein R1, R2, R3 and R4 are alkyl groups, R1, R2, R3 and R4 are the same or different, X is a halogen anion or an acid radical, and the auxiliary precipitant is preferably one or more quaternary ammonium salts; More preferably, the amount of the auxiliary precipitant added is 500ppm-3000ppm, relative to the total amount of the added alkoxysilane converted into the total mass of silicon dioxide; Further preferably, in step 5), the reaction temperature is 5-90°C, preferably 20-70°C, and the dropwise addition time of C2 to C1 is 1-30h, preferably 2-15h.

9. The preparation method according to claim 2, characterized in that: The solvent replacement in step 6) is performed by adding ultrapure water while heating to evaporate the solvent in the water, or Using ultrafiltration, while replenishing ultrapure water, concentrating until the solvent content in the silica sol is removed to below 200 ppm, preferably below 100 ppm; Preferably, the concentration in step 4) is performed by vacuum heating concentration or ultrafiltration membrane concentration to concentrate the mass fraction of the silica sol to more than 20%; More preferably, in step 6), the filtering accuracy is 0.1 μm-5 μm.

10. Use of the silica sol containing no secondary small particles according to claim 1 or the silica sol containing no secondary small particles obtained by the preparation method according to any one of claims 2 to 9 in chemical mechanical polishing.

Citation Information

Cited By

  • A spherical nano-silica sol, a preparation method and application thereof

    CN122748666A